The Charles H. Scott Gallery - Emily Carr College of Art & Design : 1985/86 Exhibitions. - Emily Carr College of Art, Granville Island, Vancouver (Vancouver : Charles H. Scott Gallery, 1986)
Schmidt, Marianna ; Straiton, Ken ; Benjamin, Max ; Chappell, Georgiana ; Sourkes, Cheryl ; Payne, Gordon ; etc
overzicht tentoonstelling 1985-1986
English
kunstcatalogus